Principled Pragmatism: VOC Interaction with Makassar 1637-68 and the Nature of Company Diplomacy - Fredrik Feddersen, Carl (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
In this study of the Dutch East India Company the author uses the Company's seventeenth century diplomatic interaction with the trading Sultanate of Macassar, on the southwestern tip of present day Sulawesi, as a case in cross cultural diplomacy. The author argues that the outlook of the Company's agents both home and overseas was pragmatic, as was the nature of the solutions to the problems they faced. In doing so, the author challenges propositions of Company ethnocentric tunnel vision in its thinking about, and practice of overseas diplomacy. He also run counter with propositions that the communication between Company agents and their Asian friends and foes represented a miscommunication caused by structural cultural barriers. The study is based on analysis of the political language of the Company at the respective levels of operation.